A novel triangular stereo model for 3D reconstruction of uniaxial MEMS-based structured light system. (July 2023) - Ye, Yuping; Hao, Siyuan; Song, Zhan; Gu, Feifei; Zhao, Juan
Abstract: Benefiting from the small size and low driven voltage of the Micro Electro Mechanical Systems (MEMS) mirror, MEMS-based structured light (SL) 3D reconstruction has recently attracted much attention. In this paper, we propose a novel triangular stereo model for uniaxial MEMS-based 3D reconstruction. Existing SL methods based on MEMS mirrors often require the construction of a look-up table(LUT), but the proposed method only requires 34 parameters for accurate reconstruction. By analyzing the anatomy of the MEMS mirror, we put forward a transition function that allows the MEMS mirror to be regarded as an inverse camera model. Then, the triangular stereo principle can be directly employed to calculate 3D information. Furthermore, we present a calibration method to obtain the parameters of our model, since MEMS mirrors can only perform unidirectional fringe projection. Extensive experiments are performed to verify the feasibility and accuracy of our proposed mathematical model and calibration method.